Religiöse Pluralitäten – Umbrüche in der Wahrnehmung religiöser Vielfalt in Deutschland - Klinkhammer, Gritt; Neumaier, Anna (transcript, 2020)
The reception and perception of religious diversity in Germany - influenced by biographical and religious-historical aspects.